The Essence of Practicing 3D Printed Models through Game-based Module in Learning Braille Quran Code among the Beginners - Hatika Kaco; Izzminhal Akmal Norhisyam; Noor Hidayah Ruslan,; Fadzidah Mohd Idris; Muhammad Amir Rafiq Rahmat; Nurhidaya Mohamad Jan; Siti Munirah Mohd; Mohd Shaiful Sajab (Human Resource Management Academic Research Societ, 2024)
Indexed by ERA